Mung beans (Phaseolus radiates L.): Utilization as components of the growth medium Bacillus subtilis - Fadhilah, Wasiyah Khusna; Saputra, Heru Agung; Baby, Nimisha (Asian Journal of Health and Applied Sciences, 2022)
Bacillus subtilis is a bacterial contaminant widely discovered in laboratories and used in educational needs. Synthetic media are relatively expensive, which makes it difficult for microbiology laboratories to meet large-scale bacterial growth media demands. This has encouraged researchers to find alternative media with cheaper and easily available prices, namely Mung Beans, which are known to contain protein nutrients that are good for bacterial growth, which is as much as 24%. The purpose of this study was to determine the potential of mung beans’ alternative media as a medium for bacterial growth. This research is a descriptive study and the sample used is 1 tube of a pure isolate of Bacillus subtilis. The variable of this research is mung beans as an alternative medium for the growth of Bacillus subtilis. The results were obtained by observed macroscopically and microscopically, followed by a carbohydrate fermentation test and an IMViC test. Then showed that the colonies growing on the alternative medium of mung beans were in accordance with the characteristics of the colonies growing on Nutrient Agar medium (control), which indicated that these characteristics were Bacillus subtilis. Based on the research that has been done, it can be concluded that there is a qualitative growth of Bacillus subtilis in mung beans alternative media, which means that mung beans alternative media has the potential as a growth medium for Bacillus subtilis.